Acetylcholinesterase inhibitory and antioxidant properties of root extract from Pueraria mirifica / Ilya Farhana Jamal Nasir - Ilya Farhana, Jamal Nasir (2018)
Pueraria mirifica or commonly known as Kwao Krua and Thai Kudzu is originated from north Thailand and known as a popular traditional medicine for woman. The Alzheimer‟s disease (AD) is progressive inexorable loss of cognitive function associated with the presence of senile plaques in the hippocampal area of the brain. The objective of this study is to determine the antioxidant and acetylcholinesterase inhibition activity of Pueraria mirifica root extracts. The thin layer chromatography was carried out to detect the chemical compounds present in the root extracts of Pueraria mirifica. Alkaloids were detected using Dragendroff‟s reagent and terpenoids with Vanillin reagent. The total phenolic and flavonoid contents was highest in methanol aqueous extracts at 10.35 mg GAE/g and chloroform extract at 1.182 mg QE/g dry extract respectively. The antioxidant activity of DPPH showed high percentage of inhibition where all extracts achieved IC50 inhibition percentage and the highest percentage of inhibition was IC50 = 1.145 in n-butanol extracts. However the percentage inhibition of metal chelating, NORSA, superoxide radical scavenging activity and FRAP are relatively low. The highest percentage inhibition of metal chelating is IC50 = 1.768 in ethyl acetate extracts, 21.54 % also in ethyl acetate extracts in NORSA and 43.167 % in n-hexane extracts in superoxide radical scavenging activity. In FRAP, methanol aqueous extract showed the highest reducing power at 0.18 mmol Fe+/g. Based on the result above, there is potential for Pueraria mirifica extract to be used as antioxidant and acetylcholinesterase inihibtion treatment.